2017
DOI: 10.1074/jbc.m116.759555
|View full text |Cite
|
Sign up to set email alerts
|

Activated Cdc42-associated kinase 1 (ACK1) binds the sterile α motif (SAM) domain of the adaptor SLP-76 and phosphorylates proximal tyrosines

Abstract: The adaptor protein Src homology 2 domain-containing leukocyte phosphoprotein of 76 kDa (SLP-76) plays a crucial role in T cell activation by linking antigen receptor (T cell receptor, TCR) signals to downstream pathways. At its N terminus, SLP-76 has three key tyrosines (Tyr-113, Tyr-128, and Tyr-145, “3Y”) as well as a sterile α motif (SAM) domain whose function is unclear. We showed previously that the SAM domain has two binding regions that mediate dimer and oligomer formation. In this study, we have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Enhanced TCR ligation at the nascent IS would activate ZAP-70 to induce classic activating LAT- PLCγ1/SLP-76 complexes. ITK, RLK and ACK (Cdc42-associated kinase 1) phosphorylate SLP-76 (refs 71 , 72 , 73 ), whereas PLCγ1 and GADs-SLP-76 mobilize calcium and activate the ERK pathway 9 11 . However, with the maturation of the IS and subsequent clustering, the cross-linking of LFA-1 (either alone or in conjunction with the TCR) would become increasing dominant with increased numbers of LAT-GRB-2 SKAP1 complexes at the expense of activating LAT-GADs-SLP-76- complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced TCR ligation at the nascent IS would activate ZAP-70 to induce classic activating LAT- PLCγ1/SLP-76 complexes. ITK, RLK and ACK (Cdc42-associated kinase 1) phosphorylate SLP-76 (refs 71 , 72 , 73 ), whereas PLCγ1 and GADs-SLP-76 mobilize calcium and activate the ERK pathway 9 11 . However, with the maturation of the IS and subsequent clustering, the cross-linking of LFA-1 (either alone or in conjunction with the TCR) would become increasing dominant with increased numbers of LAT-GRB-2 SKAP1 complexes at the expense of activating LAT-GADs-SLP-76- complexes.…”
Section: Discussionmentioning
confidence: 99%
“…ACK1 combines with Src homology 2 domain-containing leukocyte phosphoprotein of 76 kDa (SLP-76) and phosphorylates it at Tyr113, Tyr128, and Tyr145, which allows pSLP-76 to further recruit many other signaling molecules to form multimeric complexes and guarantees the differentiation of the thymus and the function of mature T cells. In addition, Thaker et al found that ACK1 could affect the movement of T cells. Exogenous ACK1 can decrease the random mobility of T cells on ICAM-1-coated plates.…”
Section: Relationship Between Ack1 and Diseasesmentioning
confidence: 99%
“…The biological functions of some domains have been reported. For instance, the SAM domain was involved with the membrane localization, dimerization, and activation of ACK1 [18, 19]. The CRIB domain mediates the interaction between ACK1 and Cdc42 [3, 20], and the PPXY motif mediates the interaction between ACK1 and WW domain [21].…”
Section: Structure and Function Of Ack1mentioning
confidence: 99%